Klasyfikacja funkcji Sejmu RP - Balicki, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article is devoted to the issue of classification of functions performed by the Sejm of the Republic of Poland after Poland’s accession to the European Union. Due to the integration, and especially the changes that took place after the Lisbon Treaty came into force, it becomes necessary to redistribute the powers exercised by the parliament. The author presents the established classification methods and justifies the need to supplement them with a new function — the European function of the Sejm of the Republic of Poland.
Keywords: Sejm; Parliament; competences; functions of the parliament; EU